Intelligent Data Analysis by a Home-Use Human Monitoring Robot - Sugaya, Shinsuke; Takayama, Daisuke; Kouno, Asuki; Suzuki, Einoshin (Advances in Intelligent Data Analysis XI, 2012)
In this paper, we argue that a home-use autonomous mobile robot is a platform for a new kind of Intelligent Data Analysis (IDA). Recent advancement of hardware and software for robotics have enabled us to construct a small yet powerful, autonomous mobile robot from components in low cost. Such a robot is able to perform machine learning and data mining in the real world for a long period, which opens a new avenue for IDA. This paper improves and studies one of our monitoring robots in detail to reveal promising directions and challenges inherent in the new kind of IDA.